Serotype Distribution, Antimicrobial Susceptibility, and Multilocus Sequencing Type (MLST) of Streptococcus pneumoniae From Adults of Three Hospitals in Shanghai, China - Li, Xin-Xin; Xiao, Shu-Zhen; Gu, Fei-Fei; Zhao, Sheng-Yuan; Xie, Qing; Sheng, Zi-Ke; Ni, Yu-Xing; Qu, Jie-Ming; Han, Li-Zhong (Frontiers in Cellular and Infection Microbiology, 2019)
Background:Streptococcus pneumoniae, a main causative agent associated with invasive and non-invasive infection in elderly population, is a major global health problem. After pneumococcal conjugate vaccines (PCV) and pneumococcal polysaccharide vaccines (PPV) were introduced, the distribution of S. pneumoniae serotypes has changed. There was currently limited data on epidemiology and status of antimicrobial resistance of S. pneumoniae in Shanghai. Objective: To determine the serotype distribution, antimicrobial susceptibility and molecular epidemiology of S. pneumoniae isolated from adults in Shanghai. Method: A total of 75 S. pneumoniae isolates consecutively collected from 2015 through 2017 were serotyped by conventional multiplex-PCR. The antimicrobial susceptibility was determined by broth microdilution method. The multilocus sequence type (MLST) was performed to estimate the molecular epidemiology. Results: The predominant serotypes among the isolates were 19F (20.00%), 3 (16.00%), 23F (9.33%), 14 (8.00%), and19A (5.33%). The prevalence of pneumococcal strains with serotypes targeted by vaccines PCV7, PCV10, PCV13, and PPV23 was 44, 45.33, 66.67, and 80%, respectively. Penicillin non-susceptible S. pneumoniae (PNSSP) accounted for 16% of the isolates examined and resistance to erythromycin, azithromycin, tetracycline, clindamycin, cefaclor and trimethoprim-sulfamethoxazole were found in 92.00, 90.67, 86.67, 81.33, 54.67, and 54.67% of isolates, with most isolates (78.67%) presenting multidrug-resistance. The top three sequence types (STs) were ST271 (17.33%), ST180 (9.33%), and ST81 (8.00%). The international resistance clone complexes Spain23F-1 (n = 4), Netherland3-31 (n = 8), and Taiwan19F-14 (n = 14) were identified. Conclusions: The S. pneumoniae isolates showed high genetic diversity in Shanghai and the prevalence of antimicrobial resistance was also high among S. pneumoniae isolates, most of which were multidrug-resistant. The spread of international resistance clones might contribute to the increase of resistant isolates. The PPV23 could protect against most pneumococcal capsular serotypes causing infection of adults in Shanghai.